Manipulative Leadership and The Effect towards Its Subordinate as Portrayed in Orson Scott Card's Novel - Sharavina Delani (NOTION: Journal of Linguistics, Literature, and Culture, 2019)
Literary works, such as novel, usually comes from the writer’s feeling; it could be the feeling of love, frustrations, angers, satisfactions, disappointments, satire, and many other feelings towards an individual, social, organizations, even the government. A novel could also be some kind of warning towards the readers so that they could be cautious if there are any similar events happen in their real life. The main objective of this research explains the American manipulative leadership and the American cultural values seen in Ender’s Game and to analyze the effect of American Manipulative Leadership towards its Subordinate shows by Ender’s Game. The researcher uses the qualitative method to analyze the primary data and the supporting data using content analysis to interpret the images, symbols, and words. This undergraduate thesis concludes two major points. Firstly, American manipulative leadership uses two values; which are risk-taking and the future, change, and progress and forgotten two other values, directness/openness/honesty and freedom of American Cultural values. Secondly, American manipulative leaderships also affect the subordinate psychological condition. And novel can also be called as a popular culture due to its enormous achievement and its consumption by the mass.